Method for analyzing structural stability of positive electrode material

Calculating the microscopic strain of the cathode material through XRD technology solves the shortcomings of the structural stability analysis method of the cathode material in the prior art, and achieves efficient and accurate structural stability evaluation.

CN119804520AActive Publication Date: 2025-04-11BEIJING EASPRING MATERIAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411999027.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

It is difficult for the prior art to effectively evaluate the structural stability of the cathode material, and the testing method has problems such as high cost, small area, low accuracy and large fluctuations.

Method used

X-ray powder diffraction (XRD) technology is used to calculate the microscopic strain of the positive electrode material, and the structural stability of the positive electrode material is evaluated by the change in the microscopic strain. The method includes calculating multiple portions of the positive electrode material, applying a stepwise increase in pressure, performing XRD tests, calculating microscopic strain changes, and determining structural stability.

Benefits of technology

The structural stability analysis of the positive electrode material with simple operation, short test cycle and representative test data is realized, and the structural stability of the positive electrode material can be more accurately evaluated.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005226385060000091
    Figure BDA0005226385060000091
  • Figure BDA0005226385060000101
    Figure BDA0005226385060000101
  • Figure HDA0005226385110000011
    Figure HDA0005226385110000011
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and particularly discloses a positive electrode material structure stability analysis method which comprises the following steps: measuring n parts of positive electrode materials, respectively adding the n parts of positive electrode materials into a mold, applying pressure intensity which is gradually increased from small to large in a one-to-one correspondence manner, then dissociating obtained tablets, correspondingly obtaining a pressurized sample, forming an initial sample by the positive electrode material which is not pressed; after carrying out equipment goniometer position calibration and instrument width calibration on an X-ray powder diffractometer, carrying out X-ray diffraction test on the initial sample and the pressurized sample by adopting the X-ray powder diffractometer to obtain X-ray diffraction data; according to the X-ray diffraction data, micro-strain corresponding to the pressurized sample is calculated, then micro-strain changes are calculated respectively, and the structural stability of the positive electrode material is determined according to the micro-strain changes. When the method is used for analyzing the material structure, the operation is simple, the test period is short, and the test data is representative.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of battery technology, and specifically relates to a method for analyzing the structural stability of a positive electrode material. Background Art

[0002] Battery positive electrode materials can be divided into polycrystalline and single crystal. Generally, polycrystalline materials exist in the form of micron-level agglomerates. There are a large number of grain boundaries inside the agglomerates. During the battery charging and discharging process, due to the anisotropic lattice change, polycrystalline materials are prone to grain boundary cracking, resulting in the breakage of secondary particles. This leads to a rapid increase in side reactions, an increase in impedance, and a rapid decrease in performance. The use of single crystal particles can reduce grain boundaries, reduce the occurrence of side reactions, and increase the compaction density, thereby increasing the energy density. However, single crystal positive electrode materials also have problems such as particle cracks and breakage leading to a rapid increase in side reactions. At present, there are relatively few test methods for evaluating the structural stability or particle strength of single crystal positive electrode materials. Commonly used test methods are: 1. Observe cracks using a scanning electron microscope after material ion milling; 2. Analyze material cracks using EBSD after material ion milling; 3. Evaluate material structure by observing material particle size and BET changes under different pressures. These methods have some disadvantages, such as high test costs, small test areas, low test accuracy, and large test fluctuations. In summary, the analysis method of the structural stability of positive electrode materials still needs to be further improved. Summary of the invention

[0003] The present application aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the present application proposes a method for analyzing the structural stability of anode materials with simple operation, short test cycle or representative test data.

[0004] This application is based on the inventor's discovery and understanding of the following facts and problems:

[0005] Polycrystalline positive electrode materials exist in the form of micron-scale agglomerates. There are a large number of grain boundaries inside the agglomerates. During the rolling of the pole pieces and the battery charging and discharging process, due to the anisotropic lattice changes, the polycrystalline positive electrode materials are prone to grain boundary cracking, resulting in the breakage of secondary particles. The main causes of cracks in single-crystal positive electrode materials include grain boundary cracks caused by volume shrinkage, excessively high calcination temperatures during high-temperature lithiation, uneven lithium ion diffusion during charging and discharging, and increased electrolyte decomposition caused by excessively high charging voltages.

[0006] Studies have shown that the charging and discharging process of the positive electrode material is not the main cause of cracks, but the rolling process of the pole piece will cause cracks. Specifically, the inventors have found that the calcination temperature of the positive electrode material during high-temperature lithiation is high, which leads to serious loss of Li / O and the generation of oxygen vacancy defects, thereby causing crystal plane slip and microcracks within the crystal. During the material crushing and dissociation or the rolling process of preparing the pole piece, microcracks also appear inside the material due to strong external force squeezing. The above situations cause material distortion due to microscopic stress inside the positive electrode material, which ultimately leads to structural instability of the positive electrode material and affects the battery life.

[0007] Furthermore, the reason why stress causes microscopic strain is mainly due to the change in the internal microstructure of the positive electrode material during the stress process. Stress refers to the ratio of the external force acting on an object to the reaction force per unit area it bears, while strain is the deformation of an object after being subjected to force. Microscopic strain refers to the microscopic deformation caused by stress inside the material. This deformation usually occurs at the microscopic scale of the material and can be measured by techniques such as X-ray diffraction (XRD). Microscopic strain is closely related to the lattice distortion of the material, which reflects the change in the microstructure of the material under stress. The specific mechanism of stress-induced microscopic strain: 1. Lattice distortion: When a material is subjected to stress, its internal lattice will be distorted, resulting in changes in the distance between atoms. This distortion will cause the displacement of the X-ray diffraction peak, so that the microscopic strain can be measured by XRD technology. 2. Dislocation and slip: Under stress, the dislocation and slip phenomena inside the material will increase. The formation and movement of these defects will cause changes in the microstructure of the material, thereby generating microscopic strain. 3. Plastic deformation: When the stress exceeds the yield point of the material, the material will enter the plastic deformation stage. In this stage, the stress increases with the decrease of the strain rate until the yield point is reached. After that, the material continues to be subjected to stress, which will cause further changes in the microstructure and produce greater microscopic strain.

[0008] Since stress causes microscopic strain, lattice distortion, dislocation or stacking fault occurs inside the crystal. This microscopic stress has no definite direction and magnitude, so the interplanar spacing changes irregularly, causing the X-ray peak to broaden. With the increasing application of X-ray polycrystalline diffraction, peak analysis is an effective way to understand lattice defects. The use of approximate function method to determine the microcrystalline size and lattice distortion value in the material can better reflect the change law of these two physical quantities. Therefore, the inventors envision using XRD test to calculate the change of microscopic strain of positive electrode materials, and evaluate the structural stability of positive electrode materials by the change amount.

[0009] In view of this, the first aspect of the present application proposes a method for analyzing the structural stability of a positive electrode material, comprising:

[0010] Measuring n portions of positive electrode materials, defining the n portions of the positive electrode materials as the first portion of the positive electrode material, the second portion of the positive electrode material, ..., the nth portion of the positive electrode material, where n is an integer greater than or equal to 5;

[0011] The first portion of the positive electrode material, the second portion of the positive electrode material, ..., and the nth portion of the positive electrode material are respectively added to the mold, and the first pressure, the second pressure, ..., and the nth pressure that increase in sequence from small to large are applied one by one, and then the obtained pressed tablets are dissociated to obtain the first sample, the second sample, ..., and the nth sample respectively, and the positive electrode material without pressure constitutes an initial sample;

[0012] After calibrating the position of the device goniometer and the width of the instrument on the X-ray powder diffractometer, the X-ray powder diffractometer is used to perform X-ray diffraction tests on the initial sample, the first sample, the second sample, ..., and the nth sample to obtain X-ray diffraction data;

[0013] According to the X-ray diffraction data, the microscopic strains T0, T1, T2, ..., T corresponding to the initial sample, the first sample, the second sample, ..., the nth sample are calculated. n , and then calculate the microscopic strain change Δ 1= T1-T0, Δ 2= T2-T1,......,Δ n= T n -T n-1 , and determine the structural stability of the positive electrode material based on the microscopic strain changes.

[0014] This application uses XRD testing to calculate the changes in the microscopic strain of the positive electrode material and evaluates the structural stability of the positive electrode material through the change amount. This analysis method is simple to operate, has a short test cycle, and the test data is representative.

[0015] In some embodiments, the positive electrode material structural stability analysis method further includes: scatter plotting the microscopic strain change and the pressure and fitting a straight line, and determining the structural stability of the positive electrode material according to the slope of the fitted straight line. This can better evaluate the structural stability of the positive electrode material.

[0016] In some embodiments, the particle size D of the positive electrode material 50 Satisfy D 50 ≤3μm, and the sampling amount of each portion of the positive electrode material is 0.5-1.5g; in other embodiments, the particle size D 50 Satisfy 3μm≤D 50 ≤7μm, and the sampling amount of each portion of the positive electrode material is 1.5-3g; in some specific examples, the particle size D of the positive electrode material 50Satisfy D 50 ≥7μm, and the sampling amount of each portion of the positive electrode material is 3-5g. This can ensure that the force is applied, so that cracks are generated and the data stability is improved.

[0017] In some embodiments, the first pressure is 50-150 MPa; in other embodiments, the first pressure is 80-120 MPa.

[0018] In some embodiments, the nth pressure is 150-900 MPa; in other embodiments, the nth pressure is 160-600 MPa.

[0019] In some embodiments, the difference between the i-th pressure and the (i-1)-th pressure is 20-200 MPa; in other embodiments, the difference is 50-100 MPa, where i is an integer from 2 to n.

[0020] In some embodiments, the step of separating the obtained pressed tablets comprises: subjecting the pressed tablets to a sieving process.

[0021] In some embodiments, the particle size D of the positive electrode material 50 Satisfy D 50 <3μm, pass through 500 mesh sieve.

[0022] In some embodiments, the particle size D of the positive electrode material 50 Satisfy 3μm≤D 50 ≤5μm, pass 400 mesh sieve.

[0023] In some embodiments, the particle size D of the positive electrode material 50 Satisfy 5μm<D 50 ≤10μm, pass through 300 mesh sieve.

[0024] This application is based on the particle size D of the positive electrode material 50 Selecting different sieve mesh numbers according to the different sieve meshes is beneficial to the dissociation of the positive electrode tablets.

[0025] In some embodiments, in the X-ray diffraction test step, the initial sample, the first sample, the second sample, ..., and the nth sample are prepared to the same height on the sample stage, thereby facilitating the reduction of test errors and improving the accuracy of test data.

[0026] In some embodiments, the device goniometer position calibration is performed using standard Si powder.

[0027] In some embodiments, the instrument width calibration is performed using standard LaB6.

[0028] In some embodiments, a copper target (Cu Kα) is used with a wavelength of

[0029] In some embodiments, the test voltage is 30-45 kV; in other embodiments, the test voltage is 40-45 kV.

[0030] In some embodiments, the test current is 40-200 mA; in other embodiments, the test current is 100-200 mA.

[0031] In some embodiments, the step size is 0.01° to 0.02°.

[0032] In some embodiments, the scanning angle is 5 to 120°.

[0033] In some embodiments, the collection time is more than 20 minutes.

[0034] Within the above test conditions, it is helpful to improve the accuracy of the analysis results.

[0035] In some embodiments, the strongest peak is stronger than 10,000 cps; in other embodiments, the three strongest peaks are stronger than 10,000 cps; in some specific examples, the four strongest peaks are stronger than 10,000 cps.

[0036] In some embodiments, calculating the microscopic strain includes: selecting all crystal planes of the X-ray diffraction data to perform a Halder-Wagner method to calculate the microscopic strain.

[0037] In some embodiments, before measuring, the positive electrode material is dried at 100-150° C. for 1-2 hours, thereby facilitating the accuracy of the test data.

[0038] In some embodiments, the positive electrode material includes at least one of a lithium battery positive electrode material and a sodium battery positive electrode material; in other embodiments, the sodium battery positive electrode material includes at least one of a transition metal oxide, a polyanionic compound, an organic polymer, and a Prussian blue material, and the lithium battery positive electrode material includes at least one of a nickel cobalt manganese oxide, a nickel cobalt aluminum oxide, a nickel manganese oxide, a lithium nickel oxide, a lithium manganese oxide, a lithium cobalt oxide, a lithium iron phosphate, and a lithium manganese iron phosphate. Therefore, the positive electrode material structural stability analysis method is universal and has a wide range of applications.

[0039] In some embodiments, the cathode material has a single crystal structure, which can be used to evaluate the structural stability of the single crystal cathode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 It is a scatter plot of different microscopic strain change data and pressure of the nickel-6 series ternary single crystal battery positive electrode material in Example 1 of the present application.

[0041] Figure 2 These are electron microscope photographs of the nickel-6 series ternary single crystal battery positive electrode material after different pressures were applied in Example 1 of the present application.

[0042] Figure 3 It is a scatter plot of different microscopic strain change data and pressure of the nickel 5 series ternary single crystal battery positive electrode material in Example 2 of the present application.

[0043] Figure 4 These are electron microscope photographs of the nickel 5 series ternary single crystal battery positive electrode material in Example 2 of the present application after applying 0 MPa and 517 MPa pressure respectively. DETAILED DESCRIPTION

[0044] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, but cannot be understood as limiting the present application.

[0045] The first aspect of the present application proposes a method for analyzing the structural stability of a positive electrode material, comprising:

[0046] Measuring n portions of positive electrode materials, defining the n portions of the positive electrode materials as the first portion of the positive electrode material, the second portion of the positive electrode material, ..., the nth portion of the positive electrode material, where n is an integer greater than or equal to 5;

[0047] The first portion of the positive electrode material, the second portion of the positive electrode material, ..., and the nth portion of the positive electrode material are respectively added to the mold, and the first pressure, the second pressure, ..., and the nth pressure that increase in sequence from small to large are applied one by one, and then the obtained pressed tablets are dissociated to obtain the first sample, the second sample, ..., and the nth sample respectively, and the positive electrode material without pressure constitutes an initial sample;

[0048] After calibrating the position of the device goniometer and the width of the instrument on the X-ray powder diffractometer, the X-ray powder diffractometer is used to perform X-ray diffraction tests on the initial sample, the first sample, the second sample, ..., and the nth sample to obtain X-ray diffraction data;

[0049] According to the X-ray diffraction data, the microscopic strains T0, T1, T2, ..., T corresponding to the initial sample, the first sample, the second sample, ..., the nth sample are calculated. n , and then calculate the microscopic strain change Δ 1= T1-T0, Δ 2= T2-T1,......,Δ n= T n -T n-1 , and determine the structural stability of the positive electrode material based on the microscopic strain changes.

[0050] This application uses XRD testing to calculate the change in the microscopic strain of the positive electrode material, and evaluates the structural stability of the positive electrode material through the change. This analysis method is simple to operate, has a short test cycle, and the test data is representative. It can be understood that the greater the change in microscopic strain, the more cracks are generated in the positive electrode material, and the worse the structural stability of the positive electrode material.

[0051] In some embodiments, the positive electrode material structural stability analysis method further includes: scatter plotting the microscopic strain change and the pressure and fitting a straight line, and determining the structural stability of the positive electrode material according to the slope of the fitted straight line. The smaller the slope (i.e., the smaller the microscopic strain change), the more stable the positive electrode material structure is, and a rapid evaluation is performed. The larger the slope, the more unstable the structure is.

[0052] In some embodiments, the particle size D of the positive electrode material 50 Satisfy D 50 ≤3μm (such as 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm or 3μm, etc.), and the sampling amount of each portion of the positive electrode material is 0.5-1.5g (such as 0.5g, 1g or 1.5g, etc.); in other embodiments, the particle size D 50 Satisfy 3μm≤D 50 ≤7μm (such as 3μm, 4μm, 5μm, 6μm or 7μm, etc.), and the sampling amount of each portion of the positive electrode material is 1.5-3g (such as 1.5g, 2g, 2.5g or 3g, etc.); in some specific examples, the particle size D of the positive electrode material 50 Satisfy D 50 ≥7μm (such as 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm or 10μm, etc.), the sampling amount of each positive electrode material is 3-5g (such as 3g, 3.5g, 4g, 4.5g or 5g, etc.). Selecting different sampling amounts according to different particle sizes is beneficial to ensure that the positive electrode material can be better stressed during the pressurization process, so that cracks are generated and data stability is improved.

[0053] In the particle size distribution, D 50 Also called the median particle size, it means that 50% of the volume of the particles is less than or equal to this value. It can be measured by a Malvern particle size tester: disperse the positive electrode material in a dispersant (ethanol, acetone or other surfactants), ultrasonicate for 30 minutes, add the sample to the Malvern particle size tester, and start the test.

[0054] In some embodiments, the first pressure is 50-150 MPa (such as 50 MPa, 80 MPa, 100 MPa, 120 MPa or 150 MPa, etc.); in other embodiments, the first pressure is 80-120 MPa (such as 80 MPa, 90 MPa, 100 MPa, 110 MPa or 120 MPa, etc.).

[0055] In some embodiments, the nth pressure is 150-900 MPa (such as 150 MPa, 200 MPa, 300 MPa, 400 MPa, 500 MPa, 600 MPa, 700 MPa, 800 MPa or 900 MPa, etc.); in other embodiments, the nth pressure is 160-600 MPa (such as 160 MPa, 200 MPa, 250 MPa, 350 MPa, 400 MPa, 450 MPa, 500 MPa, 550 MPa or 600 MPa, etc.).

[0056] In some embodiments, the difference between the i-th pressure and the i-1-th pressure is 20-200 MPa (such as 20 MPa, 50 MPa, 80 MPa, 100 MPa, 120 MPa, 150 MPa, 180 MPa or 200 MPa, etc.); in other embodiments, the difference is 50-100 MPa (such as 50 MPa, 60 MPa, 70 MPa, 80 MPa, 90 MPa or 100 MPa, etc.), where i is an integer from 2 to n.

[0057] Testing within the above-mentioned pressure range basically covers the pressure range of electrode rolling during the preparation of batteries using positive electrode materials, and also comprehensively considers the pressure range that the positive electrode material itself can withstand. This allows for a more objective and accurate evaluation of the structural stability of the positive electrode material, and the test data is more reliable.

[0058] In some embodiments, the dissociating the obtained pressed tablets includes: sieving the pressed tablets, thereby dispersing and dissociating the pressurized positive electrode material, while maintaining the pressurized state of the positive electrode material without substantially causing other effects thereon, thereby improving the accuracy of the test.

[0059] Specifically, different sieve mesh numbers can be selected according to the particle size of the positive electrode material.

[0060] In some embodiments, the particle size D of the positive electrode material 50 Satisfy D 50 <3μm, pass through 500 mesh sieve.

[0061] In some embodiments, the particle size D of the positive electrode material 50 Satisfy 3μm≤D 50 ≤5μm, pass 400 mesh sieve.

[0062] In some embodiments, the particle size D of the positive electrode material 50 Satisfy 5μm<D 50 ≤10μm, pass through 300 mesh sieve.

[0063] This application is based on the particle size D of the positive electrode material 50 Different sieve mesh numbers are selected according to the different sieve meshes, which can make the positive electrode material dispersed and dissociated better, and at the same time, all the positive electrode materials can pass through the sieve, thereby improving the accuracy of the test results.

[0064] In some embodiments, in the X-ray diffraction test step, the initial sample, the first sample, the second sample, ..., and the nth sample are prepared to the same height on the sample stage, thereby facilitating the reduction of test errors and improving the accuracy of test data.

[0065] In some embodiments, the device goniometer position calibration is performed using standard Si powder.

[0066] In some embodiments, the instrument width calibration is performed using standard LaB6.

[0067] Specifically, the specific operations of the above-mentioned device goniometer position calibration and instrument width calibration are not particularly limited and can be performed with reference to conventional techniques.

[0068] In some embodiments, a copper target (Cu Kα) is used with a wavelength of

[0069] In some embodiments, the test voltage is 30-45 kV (eg, 30 kV, 35 kV, 40 kV, or 45 kV, etc.); in other embodiments, the test voltage is 40-45 kV.

[0070] In some embodiments, the test current is 40-200 mA (eg, 40 mA, 80 mA, 100 mA, 140 mA, 180 mA, or 200 mA, etc.); in other embodiments, the test current is 100-200 mA.

[0071] In some embodiments, the step size is 0.01° to 0.02°.

[0072] In some embodiments, the scanning angle is 5 to 120°.

[0073] In some embodiments, the collection time is more than 20 minutes, for example, it can be 25 minutes, 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes or 60 minutes.

[0074] Within the above test conditions, it is helpful to improve the accuracy of the analysis results.

[0075] In some embodiments, the strongest peak has a peak strength greater than 10,000 cps (e.g., 11,000 cps, 15,000 cps, 20,000 cps, 25,000 cps, 30,000 cps, 35,000 cps, or 40,000 cps); in other embodiments, the three strongest peaks (i.e., the third peak in the XRD spectrum arranged from largest to smallest in terms of peak strength) have a peak strength greater than 10,000 cps (e.g., 11,000 cps, 15,000 cps, 20,000 cps, 25,000 cps, 30,000 cps, 35,000 cps, or 40,000 cps); In some specific examples, the 4 strongest peaks (i.e., the fourth peak in the XRD spectrum arranged from large to small in terms of peak intensity) have a peak intensity greater than 10,000 cps (e.g., 11,000 cps, 15,000 cps, 20,000 cps, 25,000 cps, 30,000 cps, 35,000 cps, or 40,000 cps, etc.).

[0076] In some embodiments, calculating the microscopic strain includes: selecting all crystal planes of the X-ray diffraction data to calculate the microscopic strain using the Halder-Wagner method. This facilitates operation and is easy to implement.

[0077] In some embodiments, before measuring, the positive electrode material is dried at 100-150° C. (such as 100° C., 110° C., 120° C., 130° C., 140° C. or 150° C.) for 1-2 hours (such as 1 hour, 1.5 hours or 2 hours). This is conducive to improving the accuracy of the test data.

[0078] In some embodiments, the positive electrode material includes at least one of a lithium battery positive electrode material and a sodium battery positive electrode material; in other embodiments, the sodium battery positive electrode material includes at least one of a transition metal oxide, a polyanionic compound, an organic polymer, and a Prussian blue material, and the lithium battery positive electrode material includes at least one of a nickel cobalt manganese oxide, a nickel cobalt aluminum oxide, a nickel manganese oxide, a lithium nickel oxide, a lithium manganese oxide, a lithium cobalt oxide, a lithium iron phosphate, and a lithium manganese iron phosphate. Therefore, the positive electrode material structural stability analysis method is universal and has a wide range of applications.

[0079] In some embodiments, the positive electrode material has a single crystal structure. Specifically, studies have found that for single crystal positive electrode materials, the charge and discharge process is not the main cause of cracks, and the pole piece rolling process is the main cause of cracks. Therefore, the method of the present application is used to evaluate the structural stability of single crystal positive electrode materials, with higher precision and accuracy, and more guiding significance.

[0080] The specific steps of the positive electrode material structural stability analysis method described in this application are as follows:

[0081] Step 1: Treat the surface moisture of the single crystal lithium battery positive electrode material, usually by drying it in a forced air oven or a vacuum oven at 100-150° C. for 1-2 hours.

[0082] Step 2: Sample weighing: weigh the processed samples according to the following standards: 50 For samples with a diameter of ≤3μm, the sampling amount is 0.5 to 1.5g; for samples with a diameter of 3μm or less, the sampling amount is 0.5 to 1.5g; 50 For samples with a diameter of ≤7μm, the sampling amount is 1.5 to 3g; for D 50 For samples with a particle size of ≥7μm, take 3 to 5g of sample. Transfer the weighed sample to the compaction mold and gently shake the mold to make the sample surface flat.

[0083] Step 3: Place the mold (13 mm in diameter) with the sample in the equipment and slowly pressurize it to different pressures (specific pressure values ​​can be 0 MPa, 74 MPa, 110 MPa, 148 MPa, 185 MPa, 221 MPa, 259 MPa, 296 MPa, 332 MPa, 369 MPa, 406 MPa, 443 MPa, 480 MPa, 517 MPa, 554 MPa, etc.), where the pressure applied by the equipment / mold area = pressure, let it stand for 30 seconds, then remove it and demold the sample. Only one pressure point can be measured at one time.

[0084] Step 4: Place the demoulded positive electrode pressed tablet into a mortar, gently dissociate the pressed tablet and use a standard sieve to sieve the particles so that the pressed tablet is completely powdered without flaky particles. Bag the processed samples, mark them and store them.

[0085] Step 5, calibrate the instrument parameters of the X-ray powder diffractometer, use standard Si powder to calibrate the position of the equipment goniometer, and use standard LaB6 to calibrate the instrument width;

[0086] Under the determined test conditions, the goniometer position and instrument width were calibrated, standard materials (Si powder, LaB6) were prepared on the sample stage, spectra were collected, instrument calibration was performed and data were saved.

[0087] Step 6: Prepare the materials with different pressures on the sample table, perform X-ray powder diffraction test under certain conditions, and save the data for analysis; the samples prepared on the sample table must be flat to ensure that the height of the samples remains consistent each time.

[0088] Step 7: Import the test data into the refinement software for data processing:

[0089] (1) First, perform peak position processing, select the maximum peak processing, and ensure that the software recognizes all peak positions;

[0090] (2) Phase identification: The PDF5+ database (International Center for Diffraction Data) is used to determine the phase, requiring the test data to be highly consistent with the card information;

[0091] (3) Add instrument width calibration data (external standard calibration width) and select all crystal planes to calculate material microstrain data using the Halder-Wagner method.

[0092] Step 8. Perform scatter plot analysis on the microscopic strain change data and pressure (0MPa, 74MPa, 110MPa, 148MPa, 185MPa, 221MPa, 259MPa, 296MPa, 332MPa, 369MPa, 406MPa, 443MPa, 480MPa, 517MPa, 554MPa, etc.) and calculate the slope.

[0093] The embodiments of the present application are described in detail below.

[0094] Example 1

[0095] A method for evaluating the structure of a single crystal lithium battery positive electrode material comprises the following steps:

[0096] Step 1: Take 12g of nickel 6 series ternary single crystal battery positive electrode material and put it into a culture dish. Put the culture dish with material into a blast oven and dry it at 120℃ for 2h. Move the dried sample into a dryer to cool and set aside;

[0097] Step 2: Sample D 50 ≤5μm, take 3g sample each time for compaction; use 1 / 10,000 analytical balance to weigh the sample to be tested, and require to weigh 3±0.0002g; transfer the weighed sample to the compaction mold, and gently shake the mold to make the sample surface flat;

[0098] Step 3: Place the mold (13mm in diameter) with the sample in the equipment and slowly pressurize it to different pressures. After standing for 30 seconds, remove it and demold the sample. Only one pressure point can be measured at one time. The pressure settings for this time are: 0MPa, 110MPa, 185MPa, 259MPa, 332MPa, 406MPa, 480MPa, 554MPa;

[0099] Step 4: Place the demoulded positive electrode tablets in a mortar, gently dissociate the tablets and use a standard sieve to sieve the particles so that the tablets are completely powdered without flaky particles. Bag the processed samples, mark them and store them. Standard sieve specifications: 400 mesh;

[0100] Step 5, calibrate the instrument parameters of the X-ray powder diffractometer, use standard Si powder to calibrate the position of the device goniometer, and use standard LaB6 diameter to calibrate the instrument width; the operation is as follows: test conditions: voltage 40kV; current 200mA; step: 0.02°; scanning angle 10-80°; acquisition time 35min;

[0101] Under the above test conditions, the goniometer position and instrument width calibration were performed, the standard materials (Si powder, LaB6) were prepared on the sample stage, the spectra were collected, the instrument was calibrated and the data were saved.

[0102] Step 6: Prepare the materials with different pressures on the sample table respectively, perform X-ray powder diffraction test under the above conditions, and save the data for analysis; the samples prepared on the sample table are required to be flat, and the height of each sample is guaranteed to be consistent;

[0103] Step 7: Import the test data into the refinement software for data processing:

[0104] (1) First, perform peak position processing, select the maximum peak processing, and ensure that the software recognizes all peak positions; perform phase identification, use the PDF5+ database (International Diffraction Data Center) to determine the phase, and require the test data to be highly consistent with the card information. This time, the selected card is: 00-062-0431 (Li Ni 0.33 Mn 0.33 Co 0.33 O2);

[0105] (2) Add instrument width calibration data (external standard calibration width) and select all crystal planes to calculate material microstrain data using the Halder-Wagner method;

[0106] The test results are shown in Table 1. Figure 1 .

[0107] Table 1 Microscopic strain data of nickel 6 series ternary single crystal battery positive electrode material in Example 1

[0108]

[0109] By applying different pressures to the positive electrode material, scanning electron microscopy was performed (refer to Figure 2 ), it can be clearly seen that with the increase of pressure, obvious cracks appear in the positive electrode material, and the number of cracks and microscopic strain change Δ n The data is proportional. This shows that the microscopic strain data of the positive electrode material can evaluate the structural stability of the positive electrode material, and the microscopic strain change Δ n The smaller the cathode material, the more stable it is.

[0110] Example 2

[0111] A method for evaluating the structure of a single crystal lithium battery positive electrode material comprises the following steps:

[0112] Step 1: Take 10g of nickel 5 series ternary single crystal battery positive electrode material and put it into a culture dish. Put the culture dish with material into a blast oven and dry it at 120℃ for 2h. Move the dried sample into a dryer to cool for standby use;

[0113] Step 2: Sample D 50 ≤5μm, take 3g sample each time for compaction; use 1 / 10,000 analytical balance to weigh the sample to be tested, and require to weigh 3±0.0002g; transfer the weighed sample to the compaction mold, and gently shake the mold to make the sample surface flat;

[0114] Step 3: Place the mold (13mm in diameter) with the sample in the equipment and slowly pressurize it to different pressures. After standing for 30 seconds, remove it and demold the sample. Only one pressure point can be measured at one time. The pressure settings for this time are: 0MPa, 74MPa, 148MPa, 221MPa, 296MPa, 369MPa, 443MPa, 517MPa;

[0115] Step 4: Place the demoulded positive electrode tablets in a mortar, gently dissociate the tablets and use a standard sieve to sieve the particles so that the tablets are completely powdered without flaky particles. Bag the processed samples, mark them and store them. Standard sieve specifications: 400 mesh;

[0116] Step 5: Calibrate the instrument parameters of the X-ray powder diffractometer, use standard Si powder to calibrate the position of the device goniometer, and use standard LaB6 diameter to calibrate the instrument width; the operation is as follows: test conditions: voltage 40 kV; current 200 mA; step: 0.02°; scanning angle 10-80°; acquisition time 35 min;

[0117] Under the determined test conditions, the goniometer position and instrument width were calibrated, standards (Si powder, LaB6) were prepared on the sample stage, spectra were collected, instrument calibration was performed, and data were saved;

[0118] Step 6: Prepare the materials with different pressures on the sample table respectively, perform X-ray powder diffraction test under the above conditions, and save the data for analysis; the samples prepared on the sample table are required to be flat, and the height of each sample is guaranteed to be consistent;

[0119] Step 7: Import the test data into the refinement software for data processing:

[0120] (1) First, perform peak position processing, select the maximum peak processing, and ensure that the software recognizes all peak positions; perform phase identification, use the PDF5+ database (International Diffraction Data Center) to determine the phase, and require the test data to be highly consistent with the card information. This time, the selected card is: 00-062-0431 (LiNi 0.33 Mn 0.33 Co 0.33 O2);

[0121] (2) Add instrument width calibration data (external standard calibration width) and select all crystal planes to calculate material microstrain data using the Halder-Wagner method;

[0122] The test results are shown in Table 2. Figure 3 .

[0123] Table 2 Microscopic strain data of nickel 5 series ternary single crystal battery positive electrode material in Example 2

[0124]

[0125] By applying different pressures to the positive electrode material, scanning electron microscopy was performed (refer to Figure 4 ), it can be clearly seen that with the increase of pressure, obvious cracks appear, and the number of cracks and microscopic strain change Δ n The data is proportional. This shows that the microscopic strain data of the positive electrode material can prove the structural stability of the positive electrode material, and the microscopic strain change Δ n The smaller the cathode material, the more stable it is.

[0126] In the description of the present application, it should be understood that the terms "first" and "nth" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "nth" may explicitly or implicitly include at least one such feature. In the description of the present application, "multiple" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0127] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0128] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A method for analyzing the structural stability of a positive electrode material, characterized in that: include: Measuring n portions of positive electrode materials, defining the n portions of the positive electrode materials as the first portion of the positive electrode material, the second portion of the positive electrode material, ..., the nth portion of the positive electrode material, where n is an integer greater than or equal to 5; The first portion of the positive electrode material, the second portion of the positive electrode material, ..., and the nth portion of the positive electrode material are respectively added to the mold, and the first pressure, the second pressure, ..., and the nth pressure that increase in sequence from small to large are applied one by one, and then the obtained pressed tablets are dissociated to obtain the first sample, the second sample, ..., and the nth sample respectively, and the positive electrode material without pressure constitutes an initial sample; After calibrating the position of the device goniometer and the width of the instrument on the X-ray powder diffractometer, the X-ray powder diffractometer is used to perform X-ray diffraction tests on the initial sample, the first sample, the second sample, ..., and the nth sample to obtain X-ray diffraction data; According to the X-ray diffraction data, the microscopic strains T0, T1, T2, ..., T corresponding to the initial sample, the first sample, the second sample, ..., the nth sample are calculated. n , and then calculate the microscopic strain change Δ 1= T1-T0, Δ 2= T2-T1,......,Δ n= T n -T n-1 , and determine the structural stability of the positive electrode material based on the microscopic strain changes.

2. The method for analyzing the structural stability of positive electrode materials according to claim 1, characterized in that: Also includes: The microscopic strain change and the pressure are scatter plotted and a straight line is fitted, and the structural stability of the positive electrode material is determined according to the slope of the fitted straight line.

3. The method for analyzing the structural stability of positive electrode materials according to claim 1, characterized in that: Meet any of the following conditions: The particle size D of the positive electrode material 50 Satisfy D 50 ≤3μm, the sampling amount of each positive electrode material is 0.5-1.5g; The particle size D of the positive electrode material 50 Satisfy 3μm≤D 50 ≤7μm, and the sampling amount of each positive electrode material is 1.5-3g; The particle size D of the positive electrode material 50 Satisfy D 50 ≥7μm, and the sampling amount of each positive electrode material is 3-5g.

4. The method for analyzing the structural stability of positive electrode materials according to claim 1, characterized in that: The first pressure is 50-150 MPa, preferably 80-120 MPa; The nth pressure is 150 to 900 MPa, preferably 160 to 600 MPa; The difference between the i-th pressure and the (i-1)-th pressure is 20 to 200 MPa, preferably 50 to 100 MPa, wherein i is an integer from 2 to n.

5. The method for analyzing the structural stability of positive electrode materials according to claim 1, characterized in that: The step of separating the obtained compressed tablets comprises: subjecting the compressed tablets to screening treatment.

6. The method for analyzing the structural stability of positive electrode materials according to claim 5, characterized in that: Meet any of the following conditions: The particle size D of the positive electrode material 50 Satisfy D 50 <3μm, pass 500 mesh sieve; The particle size D of the positive electrode material 50 Satisfy 3μm≤D 50 ≤5μm, pass 400 mesh sieve; The particle size D of the positive electrode material 50 Satisfy 5μm<D 50 ≤10μm, pass through 300 mesh sieve.

7. The method for analyzing the structural stability of positive electrode materials according to claim 1, characterized in that: In the X-ray diffraction test step, the initial sample, the first sample, the second sample, ..., the nth sample are prepared to the same height on the sample stage.

8. The method for analyzing the structural stability of positive electrode materials according to claim 1, characterized in that: The X-ray diffraction test satisfies at least one of the following conditions: The device goniometer position calibration is performed using standard Si powder; The instrument width calibration is performed using standard LaB6; The copper target Cu Kα is used, and the wavelength is The test voltage is 30-45 kV, preferably 40-45 kV; Test current 40~200mA, preferably 100~200mA; Step: 0.01°~0.02°; Scanning angle 5~120°; The collection time is more than 20 minutes; The strongest peak has a peak intensity greater than 10,000 cps, preferably the three strongest peaks have a peak intensity greater than 10,000 cps, and more preferably the four strongest peaks have a peak intensity greater than 10,000 cps.

9. The method for analyzing the structural stability of positive electrode materials according to claim 1, characterized in that: Calculating the microscopic strain includes: All crystal planes of the X-ray diffraction data are selected to calculate microscopic strain using the Halder-Wagner method.

10. The method for analyzing the structural stability of positive electrode materials according to claim 1, characterized in that: Before measuring, the positive electrode material is dried, preferably at 100-150° C. for 1-2 hours.

11. The method for analyzing the structural stability of positive electrode materials according to claim 1, characterized in that: The positive electrode material comprises at least one of a lithium positive electrode material and a sodium positive electrode material; Preferably, the sodium positive electrode material includes at least one of transition metal oxides, polyanionic compounds, organic polymers, and Prussian blue materials; Preferably, the lithium battery positive electrode material includes at least one of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel manganese oxide, lithium nickel oxide, lithium manganese oxide, lithium cobalt oxide, lithium iron phosphate, and lithium manganese iron phosphate.

12. The method for analyzing the structural stability of positive electrode materials according to claim 1, characterized in that: The positive electrode material has a single crystal structure.

Citation Information

Patent Citations

  • Method for evaluating thermal instability of ternary cathode material of lithium ion battery

    CN110031490A

  • Ternary positive electrode active material single crystal particle and lithium ion battery containing same

    CN116154150A

  • Monocrystal ternary positive electrode material and preparation method and application thereof

    CN118782770A

  • Positive Electrode Active Material Powder for Lithium Secondary Battery, Method of Preparing the Same, Positive Electrode for Lithium Secondary Battery, and Lithium Secondary Battery

    US20230086038A1